(untitled) (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: To determine the impact of a pro-active treatment approach on outcome of extremely low gestational age neonates (ELGANs; gestational age [GA] <28 weeks) born at the perinatal centre of Lucerne, Switzerland. METHODS: We assessed rates of survival, severe neonatal morbidity and neuro-developmental impairment (NDI) of all ELGANs born alive and treated at our centre between 2000 and 2009. The results were compared with published data from contemporary national and international cohorts. RESULTS: Over the 10-year study period, a total of 216 ELGANs were born alive at the perinatal centre of Lucerne. The survival rate was 74% for all live-born infants, and 81% for those admitted to the neonatal intensive care unit. Among the 160 survivors, 25% sustained at least one major neonatal morbidity; severe brain injury (i.e., periventricular/intraventricular haemorrhage grade 3 or 4 and/or cystic periventricular leukomalacia) affected 10%; moderate or severe bronchopulmonary dysplasia 16%; retinopathy of prematurity ≥ stage 3 1%; and necrotising enterocolitis 2%. Neuro-developmental outcome data at 18 to 24 months was available for 92% of all survivors: 88% had no or mild NDI, whereas moderate and severe NDI were present in 10% and 2%, respectively. CONCLUSION: When compared with published national or international data, our pro-active treatment approach to ELGANs was associated with higher or equal survival rates without increasing rates of severe neonatal morbidity or neuro-developmental impairment at the age of 18 to 24 months.